PENGEMBANGAN E-LKPD BERBASIS WEBISTE WIZER.ME MATERI SIFAT-SIFAT BANGUN RUANG - Najla Ayuditiasni Dewi; Ratih Purnamasari; Nita Karmila (STKIP Subang, 2023)
This study aims to determine the development and feasibility of the E-LKPD based on the website wizer.me material spatial properties. This study uses an R&D research approach using the ADDIE model which consists of five stages, namely Analysis, Design, Development, Implementation, Evaluation. The subjects of this study were students of class V A at Julang State Elementary School which consisted of 21 students. In the expert validation, it was declared valid as evidenced by the results of the media validation obtaining a percentage of 100%, language experts obtaining a percentage of 100%, material experts obtaining a percentage of 92%. The development of the E-LKPD based on the website wizer.me material geometrical properties obtained the